Open removal of pediatric airway foreign body: A case report and literature review. (June 2021) - Akbarizadeh, Majid Reza; Malekzadegan, Alireza; Chupani, Sima
Abstract: Background: Foreign Body Aspiration is a common finding in children diagnosed based on clinical signs and radiological studies so that timely diagnosis and successful removal of the foreign body is essential to reduce complications and mortality. Case presentation: In this study, we described a case of a 7-year old boy with a foreign airway body whose bronchoscopy was not successful in removing the foreign body, and the removal required open surgery. We also review the literature on Pediatric airway foreign bodies. Discussion: The patient was discharged in good condition after being monitored and receiving antibiotics in the pediatric ward for seven days. Conclusion: Rigid bronchoscopy involves fewer complications and is more successful in removing the foreign body in children. However, a small percentage of children require open surgery for removal, which can be attributed to the size of the FB, its shape, how long the FB stays in the airways, and the changes that follow are involved and sufficient expertise in rigid bronchoscopy. Highlights: Foreign Body Aspiration is a common finding in children. A 7- year old boy with a foreign airway body required open surgery included. Changes that follow FB are involved and sufficient expertise in rigid bronchoscopy.